Existence of solutions for fractional q-difference equations - ÜLKE, Öyküm; TOPAL, Fatma Serap (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
In this paper, we obtain some existence results for the integral boundary value problems of nonlinear fractional q-difference equations. The differential operator is taken in the Riemann-Liouville sense. Mathematics Subject Classification (2010): 39A13, 34A08, 47H10.